A construção da imagem das personagens por meio de suas interações: uma leitura do conto Ana Davenga numa perspectiva semiótica - Gerônimo, Valéria Vicente (2020)
This paper analyzes the tale Ana Davenga, by Conceição Evaristo, which is based on the theoretical postulates of Discursive Semiotics. It tells the storyof a black woman: when she dispairs, she uses her memories to understand the disappearance of her man, Davenga. The objective is to verify how the image of the characters is built from the relationship they establish with each other, and to observe Davenga's representation in the slum; it is also show the vision and the passionate relationship of this character with all the characters present in the story and to understand the role of the enunciator in the construction of the plot and the images of the characters manipulated by him. For achieving the objectives, the plot it’s going to be analyzed first, and then the characters at the narrative and discursive levels will be explained, based on the theoretical and methodological contributions of Discursive Semiotics and Sociosemiotics. When one analyze the plot and characters in the story, it is understandable that the strategies of the enunciator, which are revealed in this research, are responsible for the effects of meaning. These effects are identified in the actancial, passional, interactional and thematic-figurative paths and they allow the variety of reading plans. Indeed, it is concluded that the Discursive Semiotics method contributes to studying the works of Afro-Brazilian literature, and since Evaristo is a writer who seeks the emancipation of black people through her writing, Ana Davenga is a story that resists so many injustices with its denunciation-voice.